2022
DOI: 10.1111/fcp.12813
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin has an inhibitory effect on MCF‐7 and MDA‐MB‐231 human breast cancer cell lines by inducing autophagy and apoptosis

Abstract: The goal of this work was to see how melatonin affected Bax and Bcl‐2 expression, as well as apoptosis and autophagy, in MCF‐7 and MDA‐MB‐231 breast cancer cell lines, which have distinct hormonal sensitivities. In this study, to investigate the IC50 value of melatonin, varied melatonin concentrations were administered to MCF‐7 and MDA‐MB‐231 breast cancer cell lines. Moreover, cytotoxic activities were analyzed through MTT analysis. Five subgroups were created for both cell lines: control, IC50‐MeL, hIC50‐MeL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…This action could be due to its antioxidant activity, stimulation of apoptosis, or inhibition of angiogenesis and tumor metastasis, among others [ 127 ]. In addition, Önder et al demonstrated that treatment with melatonin increased its repressive effect on the growth of breast cancer cells by inducing cell death in vitro [ 128 ]. Therefore, melatonin could be applied as an adjuvant treatment to chemotherapy and radiotherapy, making tumor cells more sensitive to both treatments [ 126 , 129 ].…”
Section: Chronotherapy: a Promising Therapeutic Optionmentioning
confidence: 99%
“…This action could be due to its antioxidant activity, stimulation of apoptosis, or inhibition of angiogenesis and tumor metastasis, among others [ 127 ]. In addition, Önder et al demonstrated that treatment with melatonin increased its repressive effect on the growth of breast cancer cells by inducing cell death in vitro [ 128 ]. Therefore, melatonin could be applied as an adjuvant treatment to chemotherapy and radiotherapy, making tumor cells more sensitive to both treatments [ 126 , 129 ].…”
Section: Chronotherapy: a Promising Therapeutic Optionmentioning
confidence: 99%
“…Cell growth was assessed in 96-well plates at the 24, 48, and 72 h points using the methylthiazolyl tetrazolium (MTT) assay (Onder et al 2022). 100 ml of complete medium containing 5x103 cells were seeded in each well.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…The following day (day 0), cells were treated with different concentrations of HES (20,40,60, 80 and 100 µM). Cell growth was assessed at the 24, 48, and 72 h points using the methylthiazolyl tetrazolium (MTT) assay (Onder et al 2022). HES's half maximal inhibitory concentration (IC50) was determined.…”
Section: Cell Viability Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…PBS-washed coverslips were treated with DAPI for one minute, and the nuclei were stained. After the coverslips were washed again with PBS and sealed with the water-based sealer, the obtained preparations were examined under an Olympus BX51 fluorescent microscope 19 .…”
Section: Testing the Effect On Apoptosismentioning
confidence: 99%